2021
DOI: 10.3390/ani11113169
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiling of mRNAs, lncRNAs and circRNAs in Skeletal Muscle of Two Different Pig Breeds

Abstract: RNA-Seq technology is widely used to analyze global changes in the transcriptome and investigate the influence on relevant phenotypic traits. Beijing Black pigs show differences in growth rate and meat quality compared to western pig breeds. However, the molecular mechanisms responsible for such phenotypic differences remain unknown. In this study, longissimus dorsi muscles from Beijing Black and Yorkshire pigs were used to construct RNA libraries and perform RNA-seq. Significantly different expressions were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Meanwhile, the expression pro les of lncRNAs in skeletal muscle tissues were also investigated and lncRNAs were found to be differentially expressed in samples with different genetic backgrounds. However, these studies in livestock have mainly been focused on sheep [10][11][12], cattle [13][14][15], chicken [16][17][18], and pigs [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the expression pro les of lncRNAs in skeletal muscle tissues were also investigated and lncRNAs were found to be differentially expressed in samples with different genetic backgrounds. However, these studies in livestock have mainly been focused on sheep [10][11][12], cattle [13][14][15], chicken [16][17][18], and pigs [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we constructed an mRNA–miRNA–lncRNA regulatory network and found potential pathways that may regulate intramuscular fat deposition and muscle development in pigs. Similarly, a comparison of the expression profiling of mRNAs, lncRNAs and circRNAs in the LD muscle of Beijing Black and Yorkshire pigs at 210 d identified DE mRNAs that are mainly enriched in the ECM–receptor interaction, focal adhesion, AMPK signaling pathway, PI3K-Akt signaling pathway, adipocytokine signaling pathway, fatty acid metabolism, and PPAR signaling pathway [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic mechanism of meat quality-related traits has always been a popular area of research, but the molecular mechanism of fat quality has rarely been reported. RNA-seq has been widely applied to analyze gene expression patterns and identify new transcripts useful for elucidating the molecular function and regulation mechanisms in various organisms due to its high detection sensitivity and low noise [ 39 , 40 ]. In this study, to identify candidate genes and illustrate the molecular regulatory mechanisms of backfat quality, the systematic expression profiles of mRNAs and lncRNAs in backfat tissue of Beijing Black pigs with high- and low-fat quality have been compared by RNA-sequencing.…”
Section: Discussionmentioning
confidence: 99%